Improvement of the Quality of Acid Mine Dranage With Natural Zeolite with Case Study at South Sumatra - Dwi Setyawan (Institut Teknologi Bandung, 2007)
Some natural zeolite types have been exploited for long time to improve the quality of mine waste water. This research was to study the effect of natural zeolite from Lampung (Indonesia) to improve the quality of acid mine drainage from gold-mine in South Sumatra. The size of zeolite is 0,045-0,090 mm and it consist of the clinoptilolite, type. The zeolite column was made from PVC pipe with the length of 20 cm and the diameter of 10,2 cm. The zeolite column was leached in saturated condition during 12 weeks and was divided into four times intake of leached samples. Waste mine water taken from the location of Barisan Tropical Mining (Rawas gold project, Indonesia) on 21 and 23 July 1998. The water samples from pit Berenai contain relatively high iron ( 28 mg/l) and mangan of 9 mg/l, while zinc is less than 2 mg/l. The water generally very acid (pH 2,9) and contained the sulphate until 250 mg/l and the value of salinity of 28 mS/cm. The water sample from sediment pond and mining river generally contained iron, mangan and zinc lower compared to Berenai pit. Leached through zeolite column in the end of experiment contained of iron less than 1 mg/l, while manganese only a little changing. For water sample from Berenai pit, the column of zeolite reduced the sulphate content become 66 mg/l, decreased the salinity to less than 18 mS/cm, and increased the pH to 6,5 or more. The results indicated that natural zeolite from Lampung can be used to improve the quality of acid mine drainage. However, the application of the zeolite for larger scale still need detailed study.